Pengaruh Hipnoterapi terhadap Penyintas Gempa Lombok yang Menderita Kecemasan - Mustafid Amna Umary; Kartika Dwi H apsari; Rini Sugiarti; Sri Hardiani (LPPM STIKES Mataram, 2024)
Introduction: Anxiety is a response that causes feelings of helplessness. Anxiety causes confusion and distortion of perception which interferes with the learning process, concentration, ability to make associations and reduces memory. Lombok earthquake survivors experienced anxiety by displaying feelings of worry, difficulty concentrating, and cognitive distortions which had an impact on their ability to live life optimally. Clinical hypnosis or hypnotherapy is a type of hypnosis that is used for physical and psychological healing, one of which is as a medium for healing anxiety problems.Purpose: This study aims to determine the effect of giving hypnotherapy on the anxiety level of Lombok earthquake survivors.Method: The methodology in this research uses a quasi-experimental research method with a pre-test & post-test design without control group. The study population was earthquake survivors who underwent therapy sessions at the GITU clinic. The sample in the research consisted of 14 people using a purposive sampling technique. The anxiety level of earthquake survivors was measured using the Hamilton Rating Scale-Anxiety (HRS-A) instrument before and after being given hypnotherapy. Analysis of this research data used the T Test with a significance level of <.005.Results: The test results of this research show a significance value of .000, smaller than .005, indicating that hypnotherapy is effective in reducing anxiety levels. It can be concluded that there is an influence of hypnotherapy on anxiety levels in Lombok earthquake survivors.